Nghiên cứu ảnh hưởng của sự dịch chuyển các chất lưu hóa đến quá trình lưu hóa blend cao su tự nhiên-cao su EPDM (CSTN/EPDM).Phần 2. Ảnh hưởng của quá trình hỗn luyện đến sự phân bố lại các chất xúc tiến. - Đa, Lê Như; Hưng, Đặng Việt; Long, Uông Đình; Duy Linh, Nguyễn Phạm; Chương, Bùi (Vietnam Journal of Chemistry, 2016)
The migration and redistribution of accelerators in blends NR/EPDM were studied in two blending processes: cross-blending and simultaneous blending. In both blending process the curative migration obviously depend on their solution parameters and the speed of network formation in rubber phases. It was shown that examination of vulcanization curves and parameters may be successfully used for determination of curative redistribution in blends NR/EPDM. Keywords. Blend NR/EPDM, vulcanization curves, natural rubber, EPDM rubber, blending processes.